Research and design of three-phase high frequency rectifier with voltage boosting and power factor correction capability - Man, Zhiyao (2024)
With the popularization of various power electronic devices, harmonic pollution of power grid becomes more and more serious. Among them, the traditional rectifier is one of the main sources of power grid pollution. As a new generation of rectifier, three-phase voltage PWM rectifier has the characteristics of constant output voltage, unity power factor operation and low harmonic pollution. The purpose of this paper is to develop a three-phase PWM rectifier device. Firstly, the circuit structure and control principle of PWM rectifier are briefly described, and the operation modes of threephase voltage type PWM rectifier (Voltage Source Rectifier VSR) under different switching modes are analyzed. By switching function and coordinate transformation, to establish the general mathematical model of three-phase VSR and DQ(Cartesian coordinates Real part and Imaginary part) mathematical model. According to the established mathematical model, the design process of voltage and current control loop controller is introduced in detail. Secondly, the Matlab/Simulink simulation platform is used to build the simulation system model. Finally, By comparing the simulation and result analysis, the feasibility of the control scheme in this paper is verified. Based on the above process, a three-phase PWM rectifier with variable output voltage and adjustable grid side power factor was finally implemented, bringing research prospects for harmonic control in the power grid.